Investigating the Effect of Investor Pressure on Dividend Policy - Seyed Reza Seyed Nezhad Fahim; Ayat Balali; Fereshteh Hasanzadeh (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Dividend payment decisions are one of the critical components of corporate policy and one of the most important issues in the financial literature. On the one hand, they affect companies' investments. On the other hand, many shareholders with short-term investment horizons want to distribute cash dividends, so managers must constantly balance their interests and profitable investment opportunities to maximize wealth. This study examines the effect of investor pressure on dividend policy.Methodology: Eighty-four companies listed on the Tehran Stock Exchange from 2013 to 2018 were selected. Using the combined data approach, we tested the research hypotheses.Findings: The results of this study indicate that the pressure of investors has a positive and significant effect on the dividend per share and the ratio of dividends to sales.Originality/Value: Explaining the policy of profit sharing of companies and its determining factors is one of the biggest challenges that has always been faced by thinkers in the field of financial economics, which was examined in the present study.